Poverty and Legal Problems in Jordan : Defining the Relationship - Prettitore, Paul (World Bank, Washington, DC, 2015)
Jordanian citizens are no exception - a household survey conducted in Jordan in 2011 found that roughly 20 percent of families had a member experience a legal problem in the previous five years. Legal problems, left unaddressed, can cause an economic or social shock that pushes vulnerable persons into poverty. From an equity standpoint, the poor and near-poor need equal access to services that subsequently enhance opportunities to exercise their rights. Taking the equity argument a step beyond equal access to existing services, governments should develop special services that target the specific needs of the poor in resolving legal problems. Defining the relationship between legal problems and poverty is not a simple task. The first step is identifying the types of legal problems that are most likely to affect the poor and the near poor, and comparing this with wealthier citizens. The second step is to identify within this group the types of cases that are most likely to have some kind of poverty impact on the poor and near-poor. Greater knowledge of this relationship will help policymakers develop the appropriate tools to address these problems.